UTP Energy Retrofitting: Opportunities and Challenges - A'zie Syazwani Binti Khalid, A'zie Syazwani (Universiti Teknologi Petronas, 2009)
High Building Energy Index (BEI) reported for University Technology PETRONAS (UTP) shows that the building not performed as low energy buildings as claimed by the designers. Thus, this study was made to investigate the root cause of the excessive electricity consumption of UTP Buildings. Inefficient electric fixtures installed and low awareness levels on energy conservation among occupants are believes to be the major cause. The study was focused on analyzing the impact of human behaviour in utilizing the electrical appliances as compliment to OTTV research previously done by other students. Due to the restricted availability of data, 3 buildings namely Building 13,14 and Pocket C were selected to represent the whole UTP. Building survey, energy apportions and performance monitoring approach was used to investigate the root cause and potential solution to retrofit the UTP building. Once the result obtained, challenges faced and energy saving opportunities in order to retrofit UTP buildings were presented.